Consumer Participation in Infrastructure Regulation : Evidence from the East Asia and Pacific Region - Muzzini, Elisa (Washington, DC : World Bank, 2012)
Consumer Participation in Infrastructure Regulation draws on results of a survey questionnaire conducted among 45 infrastructure regulators in the East Asia and Pacific (EAP) region. It finds that EAP regulators have successfully begun to involve consumers in the regulatory process: consumer representation is a well-established practice in the region; and regulators draw on standard mechanisms to inform consumers, resolve consumer complaints, and solicit consumer input. However, regulators must take further actions to firmly move up the "ladder of consumer engagement," from merely providing information to actively consulting with consumers. In particular, consumer participation would benefit from more open disclosure policies, more effective strategies to reach out to the poor, and, tighter regulatory intervention to hold service providers accountable for resolving consumer complaints.